2017
DOI: 10.1002/slct.201701250
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Amidation of Methylarenes and Heteroamines under Metal‐Free Conditions

Abstract: Synthesis of heteroamides through oxidative amidation of methylarenes with hetero aromatic amines using tert‐Butyl hydroperoxide (TBHP) as oxidant has been described. The present method represents a significant development for the oxidative amidation of methylarenes to obtain heteroamides which does not require metal catalyst and TBHP act as only oxidant. Methylarenes are easy to handle, stable, commercially available (by‐products in gasoline industry) and used as carbonyl source for amide synthesis. The react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Based on the above results and previous knowledge, we proposed a plausible mechanism for this chemodivergent reaction. 22 As shown in Scheme 6, the reaction proceeded via the initial displacement of the halogen atom by the pyridine ring nitrogen to afford pyridinium salt (8), which subjected a facile closure and provided the shared intermediate 5aa. In protocol A, t-BuOc, which was generated in I 2 /TBHP system, 23 attacked the double bond of 5aa to afford 9, 9 subsequently transferred to 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above results and previous knowledge, we proposed a plausible mechanism for this chemodivergent reaction. 22 As shown in Scheme 6, the reaction proceeded via the initial displacement of the halogen atom by the pyridine ring nitrogen to afford pyridinium salt (8), which subjected a facile closure and provided the shared intermediate 5aa. In protocol A, t-BuOc, which was generated in I 2 /TBHP system, 23 attacked the double bond of 5aa to afford 9, 9 subsequently transferred to 11.…”
Section: Resultsmentioning
confidence: 99%
“…7 Adimurthy's group synthesized N-(pyridin-2yl)amides via oxidative amidation of methylarenes using TBHP in decane. 8 Recently, two elegant works on Cu-catalyzed aerobic oxidative C-C bond cleavage for the preparation of N-(pyridin-2yl)amide had been developed. Hwang et al reported a visiblelight-promoted aerobic oxidative C-N coupling between 2-aminopyridine and terminal alkynes through C^C triple bond cleavage (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…Pappula et al. reported an efficient TBHP‐mediated oxidative amidation of methylarenes with heteroaromatic amines, which proceeded under metal‐ and additive‐free conditions (Scheme a) . The resulting N ‐pyridyl benzamides ( 4 ) are useful building blocks for the synthesis of 2‐pyridyl urea derivatives, which exhibit various biological activities .…”
Section: Synthesis Of Amides From Methylarenesmentioning
confidence: 99%
“…Additionally, non‐reusability of the catalytic system explains the ineffectiveness of these protocols for industrial application. In spite of subtle improvements of the reaction conditions, somewhere down the line these reactions still lack versatility.…”
Section: Introductionmentioning
confidence: 99%